Protein Intake during Weight Loss Influences the Energy Required for Weight Loss and Maintenance in Cats - Vasconcellos, Ricardo S. [UNESP]; Borges, Naida C.; Goncalves, Karina N. V. [UNESP]; Canola, Julio C. [UNESP]; de Paula, Francisco J. A.; Malheiros, Euclides B. [UNESP]; Brunetto, Marcio A. [UNESP]; Carciofi, Aulus C. [UNESP] (Amer Soc Nutritional Science, 2009)
The effects of 2 diets with different protein contents on weight loss and subsequent maintenance was assessed in obese cats. The control group [Cc; n = 8; body condition score (BCS) = 8.6 +/- 0.2] received a diet containing 21.4 g crude protein (CP)/MJ of metabolizable energy and the high-protein group (HP; n = 7; BCS = 8.6 +/- 0.2) received a diet containing 28.4 g CP/MJ until the cats achieved a 20% controlled weight loss (0.92 +/- 0.2%/wk). After the weight loss, the cats were all fed a diet containing 28.0 g CP/MJ at an amount sufficient to maintain a constant body weight (MAIN) for 120 d. During weight loss, there was a reduction of lean mass in Cc (P < 0.01) but not in HIP cats and a reduction in leptinemia in both groups (P < 0.01). Energy intake per kilogram of metabolic weight (kg(-0.40)) to maintain the same rate of weight loss was lower (P < 0.04) in the Co (344 +/- 15.9 kJ.kg(-0.40).d(-1)) than in the HP group (377 +/- 12.4 kJ.kg-(0.40).d(-1)). During the first 40 d of MAIN, the energy requirement for weight maintenance was 398.7 +/- 9.7 kJ.kg(-0.40).d(-1) for both groups, corresponding to 73% of the NRC recommendation. The required energy gradually increased in both groups (P < 0.05) but at a faster rate in HP; therefore, the energy consumption during the last 40 d of the MAIN was higher (P < 0.001) for the HP cats (533.8 +/- 7.4 kJ.kg(-0.40).d(-1)) than for the control cats (462.3 +/- 9.6 kJ.kg(-0.40).d(-1)). These findings suggest that HIP diets allow a higher energy intake to weight loss in cats, reducing the intensity of energy restriction. Protein intake also seemed to have long-term effects so that weight maintenance required more energy after weight loss. J. Nutr, 139: 855-860, 2009.